HUBUNGAN ANTARA MOTIVASI KERJA, GAYA KEPEMIMPINAN, DAN KINERJA KARYAWAN - Selfiani Selfiani; Hendi Prihanto; Nani Sriyani; Dini Fitrianti (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Every company wants to have employees with high performance levels. Work Motivation and Leadership Style are considered very influential on Employee Performance. Providing Work Motivation and Leadership Style properly in accordance with sacrifice and competence to employees can improve the performance of the employees themselves. This research was conducted at PT Sahabat Jaya Grafika, Kota Harapan Indah, North Bekasi which aims to determine the relationship between work motivation and leadership style and to find out which factor between the two is very influential in improving employee performance. The author, in this study, used descriptive quantitative research methods, using correlation and regression analysis, with a sample size of 30 respondents. While the data used in this study are data obtained through the distribution of questionnaires filled out by randomly selected respondents. Furthermore, the author uses the SPSS version 22 application as a data processing tool. The results of the study, after going through the data analysis process, obtained the results that work motivation has a significant and strong influence on employee performance, namely with a determination coefficient value of 39.2% and leadership style has a significant and strong relationship with employee performance, namely with a determination coefficient value of 45.4%. Both variables have a significant influence on improving employee performance, namely with a coefficient of determination of 45.4%, and the other 54.6% comes from other factors not examined in this study. The results of the analysis also obtained a regression equation: Y=12.693+0.069X1+0.737X2. The company must pay close attention to employees and the company if it is more consistent and continues to develop in all lines so that employee work results can increase and be able to increase employee loyalty to the company.